Preparation and Evaluation of Dapagliflozin Propanediol Monohydrate-Loaded Transferosomal Dispersion for Transdermal Delivery - Mohsin Hussein Abdulameer; Khazaal Maraie, Nidhal (Iraqi Journal of Pharmaceutical Sciences, 2025)
The transdermal route of drug delivery has received significant attention in pharmaceutical research due to its ability to overcome many challenges associated with oral medication administration, including the ability to bypass first-pass metabolism, ensuring a more predictable and prolonged period of action, as well as minimizing the occurrence of adverse reactions. Transferosomes are a type of ultra-deformable lipid-based vesicles, that have the potential to offer several benefits compared to the traditional lipid-based vesicles such as liposome. The major goal of this research was to prepare (for the first time) dapagliflozin-loaded transferosomes for the purpose of minimizing the potential risk of hyperglycemia associated with oral administration for the treatment of diabetes. The transferosomes were prepared by the thin film hydration method with 5 mg of drug and different proportions of phospholipid and edge activators. The transferosomes were characterized for entrapment efficiency (EE), drug content, pH, vesicle size, PDI, zeta potential,viscosity, in vitro drug release, ex vivo permeation, FTIR and SEM. Tween 80-based transferosomes (F6) at a 95:5% w/w phospholipid:edge activator ratio yielded the highest EE (93±0.77%), drug content (99.7±1.68%), in vitro drug release within 24 hours (99±1.4%), vesicle size (105.8±1.61nm), PDI (0.436±0.01), viscosity (155±1.95 cP), and zeta potential (-35.15mV), which was selected as the optimum formula. The formula had good ex vivo permeation after 24 hours (289.8±5.2 µg/cm2, 91% drug permeated), compatible drug-excipients according to FTIR, and nano-sized spherical shape vesicles according to SEM. Three months of stability testing according to the ICH guidelines revealed that the formula was stable at 4±2C° and 25±2C°. As a conclusion, this research suggested that transferosomes can be prepared as a transdermal drug delivery system with suitable properties to be given once daily as transdermal patch for the antidiabetic drug dapagliflozin.